Catching the context: the first genre-determined reading of Francysk Skaryna’s portrait - Shutova, Olga (Knygotyra, 2022)
Лемешкин, Илья / Lemeškinas, Ilja / Lemeškin, Il’ja, Портрет Франциска Скорины. К 550-летию со дня рождения книгоиздателя / Pranciškaus Skorinos portretas. 550-ąsias gimimo metines minint / Portrait de Francisk Skorina. En commémorant le 550e anniversaire de sa naissance (1470–2020), (The portrait of Francysk Skaryna. To mark the 550th anniversary [1470–2020] of the publisher), travaux du cercle linguistique de prague, nouvelle série, vol. 10. Vilnius-Prague: Lietuvių kalbos institutas (Institut national de langue lituanienne), cercle linguistique de Prague, 2020, 298 p.; la 2e édition, revue et augumentée, 2021, 314 p.; the 3rd edition, in Lithuanian, 2022, 310 p.